PENGARUH KARAKTERISTIK INDIVIDU DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA BADAN PENGELOLAAN PAJAK DAN RETRIBUSI DAERAH UPT SAMSAT PEMATANGSIANTAR - Desyinta, Devi; Lie, Darwin; Efendi, Efendi; Putri, Debi Eka (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2019)
The result of this study can be summarized as follows: 1. Individual Characteristic and Work Environment on Employee Performance are good. 2. The analysis regression is Å¶ = 20,910 + 0,816X1 + 0,399X2 have a positive influence between individual characteristic and work environment to employee performance. 3. The correlation result of r = 0,799, the analysis correlation have a moderately high and positive correlation between individual characteristic, work environment with the employee performance. 4. The result of coefficient of determination can be explained the level of employee performance is 63.90%, and the remaining 36.10% is explained by other factors not discussed in this study. From the results of the processing and calculation of the questionnaire, the authors concluded that the individual characteristics and work environment conducted by the Badan Pengelolaan Pajak dan Retribusi Daerah UPT SAMSAT Pematangsiantar had a positive and significant effect on employee performance. This is evidenced by simultaneous hypothesis testing, where the results of the test are calculated (36,214 )> ftabel (3.23) with a significance level of 0,000 < 0,05. Keywords: Individual Characteristic, Work Environment, and Employee Performance